Rapid Exercise-Induced Mobilization of Dendritic Cells Is Potentially Mediated by a Flt3L- and MMP-9-Dependent Process in Multiple Sclerosis - Nathalie Deckx; Inez Wens; Amber H. Nuyts; Wai-Ping Lee; Niel Hens; Gudrun Koppen; Herman Goossens; Pierre Van Damme; Zwi N. Berneman; Bert O. Eijnde; Nathalie Cools (Mediators of Inflammation, 2015)
In healthy individuals, one exercise bout induces a substantial increase in the number of circulating leukocytes, while their function is transiently suppressed. The effect of one exercise bout in multiple sclerosis (MS) is less studied. Since recent evidence suggests a role of dendritic cells (DC) in the pathogenesis of MS, we investigated the effect of one combined endurance/resistance exercise bout on the number and function of DC in MS patients and healthy controls. Our results show a rapid increase in the number of DC in response to physical exercise in both MS patients and controls. Further investigation revealed that in particular DC expressing the migratory molecules CCR5 and CD62L were increased upon acute physical activity. This may be mediated by Flt3L- and MMP-9-dependent mobilization of DC, as demonstrated by increased circulating levels of Flt3L and MMP-9 following one exercise bout. Circulating DC display reduced TLR responsiveness after acute exercise, as evidenced by a less pronounced upregulation of activation markers, HLA-DR and CD86, on plasmacytoid DC and conventional DC, respectively. Our results indicate mobilization of DC, which may be less prone to drive inflammatory processes, following exercise. This may present a negative feedback mechanism for exercise-induced tissue damage and inflammation.